2009
DOI: 10.4269/ajtmh.2009.08-0469
|View full text |Cite
|
Sign up to set email alerts
|

Vector Incrimination of Sand Flies in the Most Important Visceral Leishmaniasis Focus in Iran

Abstract: Abstract. The prevalence, host preference, and rate of Leishmania spp. infection of sand fly species are important parameters for incrimination of parasite vectors. We applied polymerase chain reaction (PCR)−based and enzyme-linked immunosorbent assay (ELISA) methods to detect Leishmania spp. parasites and blood meals within individual sand flies in the most important visceral leishmaniasis (VL) focus in northwestern Iran. Leishmania spp. minicircles (kinetoplast DNA) were found in 14 (0.9%) of 1,569 female sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…Several epidemiological and entomological findings, including anthropophily and common infection of the sand flies with the same Leishmania parasite that found in patient in the same places, suggested the capacity of sand fly as a vector [17,18] . Recently, molecular techniques (PCR) have been employed for vector incrimination of sand flies [18][19][20] . The highly sensitive technique of PCR has been used for Leishmania in sand flies in some endemic areas, including Iran and India [3,4,18,19,[21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several epidemiological and entomological findings, including anthropophily and common infection of the sand flies with the same Leishmania parasite that found in patient in the same places, suggested the capacity of sand fly as a vector [17,18] . Recently, molecular techniques (PCR) have been employed for vector incrimination of sand flies [18][19][20] . The highly sensitive technique of PCR has been used for Leishmania in sand flies in some endemic areas, including Iran and India [3,4,18,19,[21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, molecular techniques (PCR) have been employed for vector incrimination of sand flies [18][19][20] . The highly sensitive technique of PCR has been used for Leishmania in sand flies in some endemic areas, including Iran and India [3,4,18,19,[21][22][23] . Results of our study revealed that the high density of P. papatasi in indoor, out door and rodent burrow resting places and its infection with L. major is attributed to the fact that this species plays a major role as a principal vector in the region.…”
Section: Discussionmentioning
confidence: 99%
“…The patients were selected from East Azarbaijan (a city located in northwest of Iran) where the Leishmania infantum is endemic (12-14), while, other species were not reported. Visceral leishmaniasis was diagnosed by an expert specialist according to medical history, laboratory findings, and clinical presentations.…”
Section: Methodsmentioning
confidence: 99%
“…The restriction fragments were subjected to electrophoresis in 3% agarose gel containing ethidium bromide (0.5 μg/ mL) for 3 h at 65 V and observed on a UV transilluminator [20,21].…”
Section: Dna Amplification and Pcr-rflpsmentioning
confidence: 99%